Songs for quintet - Wheeler, Kenny 1930-2014 (ECM-Records-Verlag, 2015)
Der britische Trompeter Kenny Wheeler (1930-2014) war einer der ganz wichtigen Instrumentalisten des Modern Jazz. Als Komponist und Improvisator setzte er Maßstäbe. Seine letzte Aufnahme machte er 2013 in den Londoner Abbey Road Studios mit seinen langjährigen Kollegen Stan Sulzmann (Saxofon), John Parricelli (Gitarre), Chris Laurence (Bass) und Martin France (Schlagzeug). "'Songs for Quintet' is a perfectly calibrated small group recording that features a set of supremely crafted compositions superbly played a well balanced and highly interactive band" (Ian Mann, www.thejazzmann.com). "Ultimately, 'Songs for Quintet' is a beautiful and poignantly subtle farewell from one of the quiet giants of jazz" (Matt Collar, www.allmusic.com).